THE ROAD TO POWER AND MADNESS (THE IRONIC FATE OF A GLOBALIZED CHINA?) - Retanan, Luis Jacob (PEOPLE: International Journal of Social Sciences, 2018)
Globalization has been fueling the peaceful reemergence of China as a great power – but it is also fueling its demise as one. In presenting that thesis, this essay will look on the connection between globalization and the rising Chinese nationalism through the conceptual lens of ontological security and historical analysis of Sinocentrism. This essay aims to understand as to how globalization has become paradoxical and problematic for China’s ambitions, considering the impact and intensity of anti-Japanese nationalist protests in China last 2012. Will its peaceful rise tragically make it a threat?